Utvärderande av nya LED-moduler avsedda för nattfjärilsfällor - Bengtsson,Sam (2025)
Due to the increasing significance of moth species’ contributions to pollination, and the relatively new advancements of AI and LED within this field of study, there is interest in developing a light trap that is both easier to get a hold of and more adapted to the conditions of a northern country like Sweden. In this study I evaluate one such LED-based Light trap and compare it to a more well-tested one made in the Netherlands. The new trap can be switched from a combined light made of white and UV-LED:s, to only utilizing its UV-LED:s, so both settings were used for 6 nights each and placed in fields together with the older model to determine the amount of catches, the diversity in species, and if there are any preferences from certain moth families. The results clearly show that in both favourable and unfavourable nights for moth activity, the older model produced in the Netherlands outperforms the newer one, and over all nights combined with the new trap set to only UV-light old traps generally had double the amount or higher in the terms of both moth quantities and species richness. The issue with the newer lights seems to stem from a lack of light intensity within the UV-spectrum, and is something that should be corrected if the trap is to ever perform on the same level as the older model. Though the newer trap is still useable right now even if it is less effective, and it could potentially be a great source of understanding for moth populations within Sweden with a little time and effort.
Keywords: Nattfjäril; LED-modul; Pollinatörer; Nattfjärilsfälla